A qualitative exploration of coaches' perceived challenges and recommendations relating to social justice in Canadian high school sport - Bishop, E.; Camiré, M. (International Sport Coaching Journal, 2025)
Sport can at once promote social justice and reinforce systemic inequities. Considering the influence coaches have on athlete development, research related to coaches` perspectives on social justice issues is warranted. The purpose of the study was to explore Canadian high school sport coaches` attitudes towards social justice. An online survey saw 392 coaches respond to six open-ended questions on perceived challenges (three questions; n = 989 responses) and recommendations (three questions; n = 724 responses) related to social justice within their teams, schools, and school boards. A content analysis led to coaches` responses being classified into three groups: (a) high school sport faces social justice issues (57.38%), (b) no social justice challenges and/or recommendations to share (39.34%), and (c) urgency regarding social justice issues is overblown (3.28%). A reflexive thematic analysis, guided by the critical positive youth development framework, was used to develop several overarching themes, highlighting persistent inequities, a lack of involvement from school boards, missed/ignored social justice issues, and a small group of antisocial justice coaches within the Canadian high school sport system. Considerations for coach education programmes and future research are discussed.